Integrated healthy lifestyle even in late-life mitigates cognitive decline risk across varied genetic susceptibility - Jun Wang; Chen Chen; Jinhui Zhou; Zinan Xu; Lanjing Xu; Xinwei Li; Zhuchun Zhong; Yuebin Lv; Xiaoming Shi (Nature Communications)
Abstract It remains unclear whether the benefits of adhering to a healthy lifestyle outweigh the effects of high genetic risk on cognitive decline. We examined the association of combined lifestyle factors and genetic risk with changes in cognitive function and six specific dimensions of cognition among older adults from the Chinese Longitudinal Healthy Longevity Survey (1998–2018, n = 18,811, a subset of 6301 participants with genetic information). Compared to participants with an unfavorable lifestyle, those with a favorable lifestyle showed a 46.81% slower rate of cognitive decline, with similar results across most cognitive domains. High genetic risk was associated with a 12.5% faster rate of cognitive decline. Individuals with a high genetic risk and a favorable lifestyle have slower cognitive decline than those with a low genetic risk and an unfavorable lifestyle. These data suggest that the benefits of a favorable lifestyle outweigh genetic factors, and therefore that adhering to a favorable lifestyle may offset the genetic risk for accelerated cognitive decline.